The Relationship between Servant Leadership, Perceived Organizational Support, Performance, and Turnover among Business to Business Salespeople - DeConinck, Jim; DeConinck, Mary Beth (Archives of Business Research, 2017)
The purpose of this study, using a sample of 382 business-to-business salespeople in the United States, was to investigate how servant leadership influences salespersons’ perceived organizational support (POS), outcome performance, turnover intentions, and turnover. The results showed that servant leadership had a direct influence on POS and performance, but was related only indirectly to both turnover intentions and turnover through POS and performance.